2017
DOI: 10.1111/cxo.12415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selective serotonin reuptake inhibitors on ocular surface

Abstract: Selective serotonin reuptake inhibitor usage might affect ocular surface by affecting tear film stability and such an association should be kept in mind by both psychiatrists and ophthalmologists in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Accumulating evidence suggests that SSRIs are closely related to the risk of DED. 8,9 Benzodiazepines and some other antidepressants, including tricyclic, noradrenergic, and specific serotonergic antidepressants, are not associated with DED. 4 Importantly, our previous study 10 indicates that SSRIs are independent risk factors for DED.…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that SSRIs are closely related to the risk of DED. 8,9 Benzodiazepines and some other antidepressants, including tricyclic, noradrenergic, and specific serotonergic antidepressants, are not associated with DED. 4 Importantly, our previous study 10 indicates that SSRIs are independent risk factors for DED.…”
mentioning
confidence: 99%
“…Both Group 1 and 2 underwent detailed psychiatric and ophthalmological examination. The results showed no significant differences between the groups in terms of age and sex (P > 0.05) (25). The most commonly used SSRI among Group 1 was fluoxetine and the period of usage ranged between 2 and 120 months.…”
Section: Psychopharmacology In Ophthalmologymentioning
confidence: 79%
“…In a cross-sectional observational study by Acan et al (2016), the authors aimed to determine the influence of selective serotonin reuptake inhibitors (SSRIs) on ocular surface and tear film stability. 36 patients (Group 1) and 36 healthy volunteers (Group 2) were enrolled (25). Group 1 was composed of patients in clinical remission of depression and/or anxiety to exclude the possible effect of the psychiatric disease on ocular disease when patients were using SSRIs.…”
Section: Psychopharmacology In Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that medications prescribed for psychiatric conditions may precipitate DED 5,6,45. Most of the antidepressant drugs, such as tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs) or serotonin–norepinephrine reuptake inhibitors (SNRIs) have antagonistic effects on muscarinic receptors, which can cause adverse effects, including DED, dry mouth and constipation 46.…”
Section: Association With Psychiatric Problemsmentioning
confidence: 99%